Chinese immigrants in Europe image, identity and social participation - Liu, Yue; Wang, Simeng 1985- (De Gruyter, 2020)
We are living in a world in which the visible and invisible borders between nations are being shaken at an unprecedented pace. We are experiencing a wave of international migration, and the diversity of migrants - in terms of how they identify, their external and self-image, and their participation in society - is increasingly noticeable. After the introduction of the Reform and Opening Up policy, over 10 million migrants left China, with Europe the main destination for Chinese emigration after 1978. This volume provides multidisciplinary answers to open questions: How and to what extent do Chinese immigrants participate in their host societies? What kind of impact is the increasing number of highly qualified immigrants from China having on the development and perception of overseas Chinese communities in Europe? How is the development of Chinese identity transforming in relation to generational change? By focusing on two key European countries, Germany and France, this volume makes a topical contribution to research on (new) Chinese immigrants in Europe
Keywords: Geschichte 1978-2018; Europe; International Migration; New Chinese Immigrants; Overseas Chinese; SOCIAL SCIENCE / General; Chinesischer Einwanderer; Europa; Aufsatzsammlung; Konferenzschrift -- 2017 -- Hangzhou; Konferenzschrift -- 2018 -- Paris